2000
DOI: 10.1037/h0087831
|View full text |Cite
|
Sign up to set email alerts
|

Forgiveness and anger-related emotions in Taiwan: Implications for therapy.

Abstract: The relationship between forgiveness and anger-related emotions was examined with an adult sample in Taiwan. Levels of forgiveness were based on the analyses in Enright, Santos, and Al-Mabuk (1989). Thirty matched pairs of level 4 (forgiveness as an obligation) and level 6 (forgiveness as moral love) participants out of 1,427 adults screened were assessed on variables of anger-related emotions via self-report, facial expressions, the frequency of casting down the eyes, and blood pressure. These measurements we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 23 publications
2
50
0
4
Order By: Relevance
“…The present studies are not the first to consider the influence of different motivations on the forgiveness process (see, e.g., Fincham et al, 2005;Huang & Enright, 2000;Worthington et al, 2001), but they do offers several theoretical extensions to previous work on these types of motivations. Whereas past studies have focused on distinct types of specific forgiveness motives (e.g., a religious obligation, desires for revenge or avoidance; see Fincham et al, 2005;Huang & Enright, 2000), we explored how forgiveness was affected by broad differences in basic self-regulatory concerns with advancement (i.e., promotion) or security (i.e., prevention).…”
Section: Motivating Forgivenessmentioning
confidence: 92%
See 1 more Smart Citation
“…The present studies are not the first to consider the influence of different motivations on the forgiveness process (see, e.g., Fincham et al, 2005;Huang & Enright, 2000;Worthington et al, 2001), but they do offers several theoretical extensions to previous work on these types of motivations. Whereas past studies have focused on distinct types of specific forgiveness motives (e.g., a religious obligation, desires for revenge or avoidance; see Fincham et al, 2005;Huang & Enright, 2000), we explored how forgiveness was affected by broad differences in basic self-regulatory concerns with advancement (i.e., promotion) or security (i.e., prevention).…”
Section: Motivating Forgivenessmentioning
confidence: 92%
“…In light of the central role self-regulation plays in forgiveness, variations in the motives that guide self-regulation could produce important variations in when and why forgiveness is granted (see Fincham et al, 2005;Huang & Enright, 2000;Worthington, Berry, Parrott, & II, 2001). The present research explores this possibility by examining how broad differences in people's self-regulatory priorities for attaining growth (i.e., promotion) versus maintaining security (i.e., prevention) affect their willingness to forgive their acquaintances, friends, and romantic partners.…”
Section: Introductionmentioning
confidence: 97%
“…Using three or four unspecified items for both forgiveness and anger, Weiner et al (1991) found that confession was associated with both forgiveness and decreased angry feelings toward the offender. Huang (1995) found that groups differing on levels of forgiveness maturity also differed on anger; however, Huang and Enright (2000) found no association between forgiveness levels and anger expression. Four studies have found that three different measures of forgiveness were associated with trait anger (Seybold et al, 2001;Berry and Worthington, 2001;Berry et al, 2005).…”
Section: Mechanisms Linking Forgiveness To Healthmentioning
confidence: 94%
“…A study by Huang and Enright (2000) examined physical indicators of negative affect (e.g., blood pressure, masked smile)…”
Section: Discussionmentioning
confidence: 99%